Creative teaching practice among islamic education lecturers: the influence of gender, age and teaching experience - Norfarahi Zulkifli; Mohd Isa Hamzah; Khadijah Abdul Razak (LPMPP Universitas Negeri Yogyakarta, 2022)
Higher education plays an important role in providing human resources that will contribute to the sustainable development of a country. Thus, lecturers are the main support to shape the students in the best way to become a good manpower in the future through a creative and effective teaching process. This study aims to identify the level of creative teaching practices among polytechnic Islamic Education lecturers in Central and Southern Zone. Furthermore, it aims to identify the influence of gender, age and teaching experience on creative teaching. In order to achieve this, questionnaire was administered online and a total of 74 respondents were involved. Data collected were analyzed through descriptive analysis of frequency, percentage and mean and inferential analysis of t-test, Pearson correlation and regression. The findings indicated that the level of creative teaching practice among Islamic Education lecturers in polytechnic is at a high level. In addition, the findings showed that that there is no significant difference in creative teaching practice according to gender, age and teaching experience. The findings can be useful for faculty members in polytechnic in ensuring that creative teaching were implemented in the teaching and learning process